Cuidados de enfermería durante la administración de medicamentos neuromusculares en pacientes críticos - Vizuete Vizueta, Alexandra Carolina (2025)
Background: the use of neuromuscular blockers (NMB) in critically ill patients will favor their well-being and recovery. These drugs are mainly administered under anesthesia to induce muscle relaxation during surgical or diagnostic procedures that require temporary paralysis of skeletal muscles. Introduction, objectives: administered during a critical intervention, their main effect is to block neuromuscular transmission by interfering with the action of acetylcholine on the nicotinic receptors of the motor plate, thus preventing muscle contraction. Types of neuromuscular blockers such as non-depolarizing blockers will act as antagonists which means that they block the action on the muscle receptors without activating these receptors, e.g. vecuronium. Depolarizing blockers are drugs that have a different mechanism of action, as they mimic and bind to the receptor, causing prolonged depolarization of the muscle membrane. They initially cause muscle contractions, but then prevent further depolarization, resulting in muscle paralysis. Methods and results: General anesthesia induction facilitates tracheal intubation and provides muscle relaxation during surgery. Mechanical ventilation in critical situations is used to facilitate controlled breathing in patients who are unable to breathe on their own. Severe or difficult-to-intervene seizure treatments may be used to control muscle movements. Interactions of BNM drugs with other drugs, such as anesthetics, antibiotics, or calcium channel blocking agents may have effects on respiration since BNMs cause muscle paralysis, they also paralyze respiratory muscles, due to this phenomenon assisted ventilation equipment should be used. Conclusions: There are also high cardiovascular risks that can cause changes in heart rate blood pressure, or even arrhythmias, Hypersensitivity of allergic people to some BNM, require tests prior to proper administration. The administration of neuromuscular blockers should be properly supervised by designated professionals.